Student Response to the Innovation of Creating Steam-Based E-Books in the Early Childhood Creativity Development Course - Heri Hidayat; Kawuryansih Widowati; Dikha Puspitasari Zakiyya; Luthfiyah Hasna; Luthvia Nur Sa'diyyah (Universitas Pendidikan Ganesha, 2023)
Digital media can facilitate the implementation of learning and help students be literate about technology. This study aims to analyze student responses regarding the use of book creators to fulfill digital learning media innovations. This research belongs to the type of qualitative research with descriptive analysis method. The subjects involved in this study were 54 students. Data collection used observation, interviews, documentation, and questionnaires, with research instruments in the form of observation guidelines, interviews, and questionnaires. The results showed that 100% of students knew about book creators. 87% of students stated that e-book design innovations were interesting. 66.7% stated that the development of creativity through science is understandable. 70.4% stated that the development of creativity through technology is understandable. 72.2% stated that the development of creativity through engineering is understandable. 68.5% of the development of creativity through art can be understood. 79.6% stated that the development of creativity through mathematics is understandable. It was concluded that there are innovations in creating e-books through book creators. It is reflected in the content of e-books which are attractively designed and based on STEAM. Student responses prove that students understand making e-books using book creators, and students can develop creativity through science, technology, engineering, art, and mathematics in a more interesting way so they are easy to understand.